HUMAN CAPITAL OF THE UKRAINIAN ECONOMY: THE IMPACT OF WAR AND POST-WAR RECOVERY POTENTIAL - HALUSHKA, Zoia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article explores the conditions and mechanisms for increasing human capital as the potential for post-war recovery in Ukraine. It analyzes theoretical and applied research on the essence of human capital as an economic resource and as the potential for post-war recovery of the Ukrainian economy. The impact of war on the components of Ukraine’s human capital is identified. The issue of forced migration of the workforce and its impact on Ukraine’s GDP loss is examined. The problem of unemployment and the reasons for it under wartime conditions are analyzed. Global trends in human capital development are studied, emphasizing the need for changes in organizational management systems to analyze and consider employees’ skills, unleash their potential, change forms of communication and organize their work, stimulate creativity, and responsibility at work. It is noted that in the current and post-war period, in human resource management, it is necessary to: review traditional management approaches, build relationships in organizations based on co-creation and balancing interests, focus on the human component of sustainable development, consider and prevent risks associated with people management, constantly search for new solutions for people management, and be prepared for new challenges. Regarding the employees themselves, it is emphasized the need to consider future changes in employment structure and skill requirements, as self-organization and self-motivation skills, ability to communicate with multiple counterparts, ability to use modern information opportunities for development, acquisition of "peaceful" professions instead of military qualifications will be most needed in the future. Attention is paid to gender aspects of human capital utilization in the post-war period, as the importance of women’s work will objectively increase due to direct military losses of able-bodied men.